Relevansi Pasal 29 Konstitusi Terhadap Sila Pertama Pancasila Sebagai Dasar Negara - Zainul Akmal (Universitas Islam Indonesia, 2018)
AbstractThis study examined the relevance of norms in Article 29 of the 1945 Constitution of the Republic of Indonesia to the principle of Belief in the One and Only God in Pancasila as the state philosophy and an answer to faith crisis. The research aimed to identify the relevance of Article 29 of the 1945 Constitution of the Republic of Indonesia to the principle of Belief in the One and Only God in Pancasila and its feasibility as the highest constitution of the state to overcome the current social problem (crisis of faith). This was normative research with a philosophical approach and a descriptive qualitative analysis model. The study concluded that, first, Article 29 of the 1945 Constitution of the Republic of Indonesia is no longer relevant to the principle of Belief in the One and Only God in Pancasila. Secondly, Article 29 is no longer relevant to answer the issue of faith crisis because the norms do not regulate such matters.Keywords: Faith; crisis of faith; state philosophy AbstrakPenelitian ini mengkaji relevansi norma dalam Pasal 29 UUD NRI 1945 terhadap sila KeTuhanan Yang Maha Esa Pancasila sebagai dasar negara dan menjawab krisis keber-Tuhanan. Tujuan penelitian ini untuk mengetahui relevansi Pasal 29 UUD NRI 1945 terhadap Sila ke-Tuhanan Yang Maha Esa dalam Pancasila dan kelayakannya sebagai konstitusi tertinggi negara dalam mengatasi permasalahan sosial yang terjadi saat ini (krisis keber-Tuhanan). Jenis penelitian adalah normatif, dengan pendekatan filosofis dan model analisis deskriptif kualitatif. Penelitian ini menyimpulkan pertama, Pasal 29 UUD NRI Tahun 1945 tidak relevan lagi dengan Pancasila, sila ke-Tuhanan Yang Maha Esa. Kedua, Pasal 29 tidak relevan lagi dalam menjawab permasalahan krisis keber-Tuhanan karena normanya tidak mengatur hal demikian. Kata-kata Kunci: Ke-Tuhanan; krisis keber-tuhanan; dasar negara